Intuitive and Counterintuitive Morality - Kahane, G (Oxford University Press, 2014)
Recent work in the cognitive science of morality has been taken to show that moral judgment is largely based on immediate intuitions and emotions. However, according to Greene’s influential dual process model, deliberative processing not only plays a significant role in moral judgment, but also favours a distinctive type of content—a broadly utilitarian approach to ethics. This chapter argues that this proposed tie between process and content is based on conceptual errors, and on a misinterpretation of the empirical evidence. Drawing on some of the author’s own empirical research, the chapter will argue so-called “utilitarian” judgments in response to trolley cases often have little to do with concern for the greater good, and may actually express antisocial tendencies. A more general lesson of this argument is that much of current empirical research in moral psychology is based on a far too narrow understanding of intuition and deliberation.